HUBUNGAN KOMUNIKASI INTERPERSONAL GURU-SISWA DENGAN MINAT BELAJAR SISWA DI SMA TRI BAKTI PEKANBARU - Fransisca, Winda; Eddison, Ahmad; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the lack of visible movement of the teacher's body when teaching so that the atmosphere of learning becomes tense as the appearance in the teaching process looks stiff. In the learning process some teachers cannot master the class because it only stays at one point. In the learning process, some teachers in explaining the material in front of the class in a voice that is not strong so that students who are behind not too hear the explanation delivered. This study aims to determine the level of teacher-student interpersonal communication in Tri Bhakti Pekanbaru High School. To find out the level of students' interest in learning in the learning process at Tri Bhakti Pekanbaru High School. To find out the relationship between teacher-student interpersonal communication with student interest in the Tri Bhakti Pekanbaru High School. This research is quantitative descriptive. The population in this study were all students at Tri Bhakti Pekanbaru High School. The sample taken in this study is proportional random sampling. Where the number of samples taken 25% of the population so that the number of samples amounted to 81 respondents. Then the data analysis technique uses Product Moment correlation techniques. Based on the results of the study showed the Frequency Distribution of Interpersonal Communication Variables (X) is categorized Very Good, which is 81.4% which is in the range of 75.01% - 100%. Based on the results of the Variable Frequency Distribution of Learning Interest (Y) is categorized Very Good, which is 75.79% which is in the range of 75.01% - 100%. The relationship of teacher-student interpersonal communication with student learning interest in Tri Bhakti Pekanbaru High School is seen from the results of Product Moment Correlation Test rxy = 0.702, where the relationship is strong or high which is in the range of 0.60 - 0.799.Key Words: Interpersonal Communication, Learning Interest